Iyouth Leadership Guard: Preferences for Entrepreneurship as a Way to Influence Careers and Civil Society - Muna, Naily El; Ashlihah, Ashlihah; Auliya, Devi (Dinar : Jurnal Ekonomi dan Keuangan Islam, 2024)
Teens should equip themselves with the abilities and interests that will make them desirable employees. Three interconnected elements that belong to the owners of rights are required to execute youth engagement in the formation of civil society (children and youth). First and foremost, young leadership is required as the forefront of self-worth to assist teens in developing into self-assured individuals that generate teamwork strength to fulfill their responsibilities. Second, educational institutions still need to encourage and facilitate the interest of teenagers in entrepreneurship in society. Analyzing teenage leadership and entrepreneurial preferences in the context of professional empowerment and civil society is the goal of this study. This study employed a mixed method, which combines quantitative and qualitative techniques. The study's conclusion is that entrepreneurship programs in learning environments are very beneficial for students' career development after they have finished their coursework.